Steady-state throughput discrete model of multipath TCP based on linked increase algorithm. (2018) - Huang, Hongcheng; Sun, Xinran; Hu, Min
This paper established a discrete model for the steady-state throughput of multipath TCP (MPTCP), which is based on linked increase algorithm (LIA) and is presented to analyse the relationship between subflow performances and throughput capacity under the steady-state bulk transmission of MPTCP data. With consideration of the coupling of subflow congestion windows' changes, the characteristics of subflow in states such as the congestion avoidance, fast recovery timeout retransmission and slow start was analysed. Furthermore, by calculating the expectations of transmitted packet number and transmission duration in a given MPTCP connection, the discrete model of MPTCP steady-state throughput can be established. Simulation results show that the proposed model can achieve the improved accuracy and robustness when predicting the steady-state transmission throughput of MPTCP.